Geological controls on the accumulation of shale gas: A case study of the early Cambrian shale in the Upper Yangtze area. (September 2019) - Zhao, Jianhua; Jin, Zhijun; Hu, Qinhong; Liu, Keyu; Liu, Guangxiang; Gao, Bo; Liu, Zhongbao; Zhang, Yuying; Wang, Ruyue
Abstract: The results of sedimentological, mineralogical, geochemical and petrophysical studies on the early Cambrian shale in the Upper Yangtze area are summarized to provide insights on the paleoenvironmental conditions, diagenetic evolution and preservation conditions that give rise to shale gas accumulation. The lower Cambrian organic-rich Qiongzhusi shale is mainly developed in the outer shelf facies of an intracratonic sag [average total organic carbon (TOC): 1.3–2.5%] and in the southeast margin (average TOC: 3.5–5.5%) of the Upper Yangtze area. The thermal maturity values (Reqv ) of the Qiongzhusi shale range from 2.19 to 4.23%, while first increasing and then decreasing from the center of the Sichuan Basin outward. The average porosities of the Qiongzhusi shale from the outer shelf facies association (FA5) in the intracratonic rift range from 1.5 to 3.41%, and those from the outer shelf facies association (FA4) in the southeast Sichuan and Guizhou areas range from 1.32 to 2.56%. The organic matter (OM) content and the development degree of OM pores are the main factors that control the porosity and pore structure of the Qiongzhusi shale. For the outer shelf deposits in the intracratonic rift, a quartz (detrital origin) content ranging between 25 and 35% is most favorable for providing an effective support framework for OM pore development due to the mixture of brittle and clay minerals. For the outer shelf deposits in the southeastern margin of the Upper Yangtze area, the high OM content and poor compaction resistance cause a poor development of OM pores, with a smaller average pore diameter than that in the outer shelf shale of the intracratonic rift. In addition, the carbonization of OM in the overmature Qiongzhusi shale change the microstructure and decrease the OM pore volume. Due to poor preservation conditions, the gas content is generally low in the organic-rich shale in the eastern and southeastern parts of the Upper Yangtze region. The Qiongzhusi shale in the interior of the Sichuan Basin, with good preservation conditions, high pressure coefficients, and high gas contents, is a favorable area for shale gas accumulation and potential exploitation. Highlights: The organic-rich Qiongzhusi shale mainly developed in outer shelf. The content of OM and the development degree of OM pores control the pore structure. A high TOC content leads to a poor development degree of OM pores in siliceous shale. The Qiongzhusi shale in the interior of the Sichuan Basin is favorable for shale gas accumulation.